Indigenous Australians and the National Disability Insurance Scheme - Biddle, Nicholas, Dr; Al-Yaman, Fadwa; Gourley, Michelle; Gray, M. C. (Matthew C.); Bray, J. Rob; Brady, Brendan; Pham, L. A. (Le Anh); Williams, Emma (Professor); Montaigne, M. (Maxine) (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research), 2014)
The National Disability Insurance Scheme (NDIS) is one of the major policy innovations of the early 21st century in Australia, representing a new way of delivering services to people with a disability and those who care for them.